Near-infrared light-sensitive liposomes for enhanced plasmid DNA transfection - Wiraja, Christian (2021)
Near-infrared (NIR) light-responsive liposomes are attractive carriers for targeted and controlled drug delivery to the superficial organ or tissue (e.g., skin). This work describes the development of NIR-responsive liposomes by incorporating gold nanostars within liposomes composed of Phospholipon 90 g and cholesterol. Following cellular delivery, photothermal effect around the gold nanostar upon NIR stimulation induces microcavitation and liposome phase transition which consequently triggers the release of encapsulated molecules. Taking GFP plasmid as an example, we demonstrate enhanced gene transfection into fibroblasts following NIR treatment.